Hierarchical Hybrids of Mesoporous NiCo2O4 Needles/Graphene/Carbon Nanotubes with High Performance for Lithium Ion Batteries and Oxygen Reduction Reactions. Issue 12 (18th October 2016) - Yan, Yan; Liu, Yuqing; Ni, Weiyan; Wu, Jinyan; Liu, Mingkai; Liu, Tianxi
Abstract: Three‐dimensional (3D) hierarchical NiCo2 O4 ‐graphene/carbon nanotube (NiCo‐G/CNT) hybrids with NiCo2 O4 needles deposited on a conductive G/CNT template have been facilely produced by a co‐precipitation method. Mesoporous NiCo2 O4 needles endow the NiCo‐G/CNT hybrids with high specific surface area, which allows good electrolyte penetration and large electrode–electrolyte contact area, leading to fast ion and electron transfer and excellent strain accommodation. The unique hierarchical structures of NiCo‐G/CNT hybrids ensure complete exposure of their active sites and endow them with dual functionalities that allow them to serve as high‐performance electrodes for both lithium‐ion batteries and oxygen reduction reactions. In particular, the NiCo4‐G/CNT sample delivers a remarkable specific capacitance of 1392 mAh g −1 at current density of 0.1 A g −1, and achieves high electrocatalytic activity with long‐term stability for ORR. This preparation strategy is simple and effective, and can be conveniently extended to fabricate other kinds of binary‐oxide‐based materials for energy‐storage applications. Abstract : Hierarchical NiCo2 O4 ‐graphene/carbon nanotube (NiCo‐G/CNT) hybrids with NiCo2 O4 needles deposited on a conductive carbonic G/CNT template deliver excellent performance in lithium ion batteries and oxygen reduction reactions due to their porous structures, full exposure of active sites, and rapid electron transfer inside the hybrids.